2006
DOI: 10.1111/j.1365-2591.2006.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the surface free energy on root canal dentine walls treated with chelating agents and NaOCl

Abstract: Use of chelating agents alone or in combination with NaOCl decreased the wettability of root canal wall dentine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
4
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 23 publications
6
63
4
3
Order By: Relevance
“…The superior adaptation of AH Plus could be due to its ability to bond to root dentin chemically by reacting with any exposed amino groups in collagen to form covalent bonds between the epoxy resin and collagen 28) . Unlike alkaline bioceramic-based sealers 36) , AH Plus is slightly acidic and might result in selfetching when in contact with dentin, thereby enhancing interfacial bonding and adaptation 37) . Furthermore, the alkaline nature of many bioceramic by-products has been reported to denature dentinal collagen fibers, which then facilitated the penetration of sealers into the dentinal tubules 12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The superior adaptation of AH Plus could be due to its ability to bond to root dentin chemically by reacting with any exposed amino groups in collagen to form covalent bonds between the epoxy resin and collagen 28) . Unlike alkaline bioceramic-based sealers 36) , AH Plus is slightly acidic and might result in selfetching when in contact with dentin, thereby enhancing interfacial bonding and adaptation 37) . Furthermore, the alkaline nature of many bioceramic by-products has been reported to denature dentinal collagen fibers, which then facilitated the penetration of sealers into the dentinal tubules 12) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, despite the manufacturer of EndoSequence BC claiming that the product contains no polymers, independent researchers had identified the presence of carbon polymer which had not been previously reported by the manufacturer 36) . EDTA (17%) was used as an irrigant in this study, as it had been demonstrated to decrease the wetting ability of dentinal walls 37) , thereby producing an environment suitable for the adhesion of hydrophobic materials such as AH Plus. Therefore, the hydrophobicity of AH Plus sealer facilitated the permeation of resin into the open dentinal tubules and created efficient micro-retention 38) .…”
Section: Discussionmentioning
confidence: 99%
“…O Pulp Canal Sealer EWT, que é um cimento com alto padrão de escoamento, teve grande dificuldade de se espalhar na superfície dentinária, visto que a smear layer formada dificultou este escoamento por criar uma superfície de menor rugosidade quando comparada àquela com os túbulos dentinários patentes. De acordo com a lei de Wenzel, quanto maior a rugosidade, maior a capacidade de escoamento de um líquido sobre um sólido 22,23 .…”
Section: Discussionunclassified
“…Al realizar la evaluación por SEM (microscopía electrónica de barrido), se observó que no hubo remoción del barrillo dentinario, lo cual confirmó que los irrigantes por sí solos no son suficientes para remover el componente orgánico e inorgánico del conducto radicular. Algunos autores han recomendado que el uso de soluciones irrigantes debe ser complementado con un protocolo de irrigación [17,18].…”
Section: Discussionunclassified